Impulsive Buying Behaviors of Youth Generation Customers at Fashion Retailers in Nepal - Sah, Gunja Kumari; Pokharel, Shiva Prasad (Patan Pragya, 2023)
This research paper aims to explore the phenomenon of impulse buying in the fashion retailer. The study examines situational and personal factors to determine which factor was perceived as leading to more impulsive buying. The study considered a quantitative deductive research approach. Research questionnaires were proposed by visiting and distributing the customers with 350 valid responses for data collection by purposive sampling techniques. Only the Youth (Y) generation was considered for the research work. The results were constrained by the sampling strategy, sample size, and assessment of the influential variables. The purchase urge was more strongly influenced by situational factors rather than personal factors. Therefore, fashion retailers must carefully decide on situational factors to encourage customers to impulse purchase.